Critique of Ifeanyi Menkiti's Idea of Person and Community (Global Journal of Human-Social Science, 2021)
We are in a society where its system permits an individual to take precedence over a group/community; the reason why we often put wealth above good character. In Africa, some scholars, text and philosophers have attributed this social woe on imperial influx that took over African traditional institution around 19th century. In his quest to search for socio-cultural, metaphysical, epistemic and moral constituents of a person, Ifeanyi Menkiti, a prolific African philosopher gave a turgid articulation on the Person and Community in African Traditional Thought, with a sharp position that a community/group takes precedence over a person/individual. Put difference, it is a community that defines an individual. This paper therefore is committed to review and critically examine contents in this Menkiti's radical communitarian position. Doing this, we shall examine the essence of a person/individual (with a special focus on metaphysical, epistemic and moral constituents of a person), the process of incorporation in traditional African society, and the idea of depersonalization. This paper assumes that Menkiti's failed to acknowledge the roles of an infant and the dead (ancestors) in the organization and development of a community.
Keywords: individual; personhood; community; incorporation